Development of an Optimal Scaffolding Model for Problem-Based Learning in Vocational Schools in Bekasi City - Setyowati, Arum; Rusmono, Rusmono; Djatmiko, Wisnu (Peneliti.net, 2024)
Problem-Based Learning (PBL) facilitates student learning through group activities and self-directed learning (SDL) to formulate problems related to the competencies to be achieved. The problems collaboratively formulated by all group members are studied in search of solutions. The problems provided by the teacher are unstructured, meaning there is not just one solution but several potential alternatives. SDL requires various types of diligence or student skills. Students who succeed in learning through PBL largely depend on the amount of appropriately personalized support they receive and their confidence in overcoming their shortcomings with that support (Smith & Cook, 2012). However, vocational school (SMK) teachers, especially in technology and engineering, have not yet found ways to provide scaffolding to students learning through PBL to face their optimal challenges. This situation arises because vocational school teachers generally position themselves as facilitators in PBL learning rather than forming a PBL tutor team. This research aims to develop a scaffolding design for SMK students in technology and industry to tackle optimal challenges. Scaffolding focuses on enhancing students' problem-solving skills by providing timely support (Wood et al., 1976). The formative evaluation phase is divided into three parts: one-on-one evaluations by experts and learners, small group evaluations, and field trials. The results of the one-on-one evaluations by experts, consisting of content and media specialists, yielded average scores of 88.49% and 95.42%, respectively, both rated as very feasible. This indicates that the learning materials for the Scaffolding of Optimal Challenges in the PBL subject of Programming and Microcontroller Applications are indeed suitable for use in the learning process within Technology and Engineering SMK environments in Bekasi City.